Tweeting in Disaster Area: An Analysis of Tweets during 2016 Major Floods in Indonesia - Anang Dwi Santoso (Policy & Governance Review, 2017)
Social media allows people in the disaster area to communicate disaster information, to the people outside the disaster area, more quickly and accurately. Unfortunately, there are limited researches that examine the use of Twitter by people in the disaster sites. This study aims to explore the use of Twitter by users in the disaster-affected areas. We use the feature of twitter geolocation, to separate information from inside and outside the disaster site. This research gives depiction about communication behavior of people in the affected disaster area, through social media. The result showed that people in disaster location use twitter to give first-hand report, coordinate rescue effort, provide help and express grief. In addition, by focusing on the affected area, Twitter used by lay people is usually found rather than other users. From the segment of time, the researcher finds a number of tweets that will increase each day. Users will share more information the days after rather, than the day of disaster. In practical term, this research explores the used of social media by the victims of disaster, which can encourage effective communication to people or group outside the location; theoretically, this research gives more detail understanding about shared information from the people in the disaster place.